2022
DOI: 10.21203/rs.3.rs-1404755/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing Knowledge of First Aid Management of Burns Amongst Syrian Private University Students.

Abstract: Background:Burn related injuries (BRIs) are relatively common, mostly accidental, and highly preventable forms of injury. First aid management of BRIs can have a significant impact on the outcome and morbidity of these injuries, yet there seems to be an inadequacy in the knowledge related to burn management worldwide. Hence, our study aimed to delineate the level of knowledge and awareness of burn first aid treatment (BFAT) amongst undergraduate students, and the impact training courses had on that knowledge.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 10 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…From a global perspective, based on a study of 152 students done at the medical college in Mangalore city, south India, in 2011, only 11% of them had previous first aid training. A total of 13% of students had good knowledge, 68.4% of students had moderate, and 17.8% of students had poor knowledge of first aid [ 10 , 11 ]. An additional study carried out at Vydehi Medical College in Bangalore found that 150 medical students filled out the questionnaire, 50 from each of 5 th (2 nd year), 7 th (3 rd year), and 9 th terms (4 th year).…”
Section: Introductionmentioning
confidence: 99%
“…From a global perspective, based on a study of 152 students done at the medical college in Mangalore city, south India, in 2011, only 11% of them had previous first aid training. A total of 13% of students had good knowledge, 68.4% of students had moderate, and 17.8% of students had poor knowledge of first aid [ 10 , 11 ]. An additional study carried out at Vydehi Medical College in Bangalore found that 150 medical students filled out the questionnaire, 50 from each of 5 th (2 nd year), 7 th (3 rd year), and 9 th terms (4 th year).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of analysing the full texts of the publications, twenty-one studies were discarded due to inadequate methodology or outcomes, and fifteen studies were discarded due to insufficient data. Finally, thirteen studies 26,65,66,[70][71][72][73][74][75][76][77][78][79] remained in this systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
“…Among them, 62.24% were female and 77.67% were medical students. The studies included in this systematic review were conducted in Saudi Arabia (n = 6), 66,[71][72][73][74]77 Pakistan (n = 3), 26,76,79 Syria (n = 2), 65,78 Egypt (n = 1), 70 and Malaysia (n = 1). 75…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations